2020
DOI: 10.1021/acs.nanolett.9b05029
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ion Sweeping on Prussian Blue Analogue Nanoparticles and Activated Carbon for Electrochemical Kinetic Energy Harvesting

Abstract: Kinetic energy is an ideal energy source for powering wearable devices or internet of things (IoTs) because of its abundant availability. Currently, most kinetic energy harvesting systems are based on friction or deformation, which require high-frequency motion or high material durability for sustainable energy harvesting. Here, we introduce selective ion sweeping in a hybrid cell consisting of an ionadsorbing activated carbon and an ion-hosting Prussian blue analogue nanoparticle for electrochemical kinetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Sustainable, efficient, and economical electrochemical energy storage technologies are efficient to power electric vehicles and satisfy the ever-increasing demand for electronic devices. Two-dimensional (2D) materials possessing an ultrathin conductive structure, superior electrochemical stability, and tunable electronic properties have exhibited excellent application potential in many fields such as catalysis, battery, supercapacitor, sensor, separation technology, and bioengineering. Thus, the electrode based on 2D materials such as graphene, transition metal dichalcogenides as well as MXenes, borophene, arsenene, antimonene, germanene, phosphorene, and stanine are regarded to endow an electrochemical actuation property. It is found that the inherent advantages of 2D materials not only afford fabulous reactivity but also accelerate ion diffusion during repeated charge–discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable, efficient, and economical electrochemical energy storage technologies are efficient to power electric vehicles and satisfy the ever-increasing demand for electronic devices. Two-dimensional (2D) materials possessing an ultrathin conductive structure, superior electrochemical stability, and tunable electronic properties have exhibited excellent application potential in many fields such as catalysis, battery, supercapacitor, sensor, separation technology, and bioengineering. Thus, the electrode based on 2D materials such as graphene, transition metal dichalcogenides as well as MXenes, borophene, arsenene, antimonene, germanene, phosphorene, and stanine are regarded to endow an electrochemical actuation property. It is found that the inherent advantages of 2D materials not only afford fabulous reactivity but also accelerate ion diffusion during repeated charge–discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…,) as well as water molecules. 190–193 Fig. 11d depicts the visualization of PBA as a host structure supporting the concept.…”
Section: Future Perspectivesmentioning
confidence: 76%
“…The systems could effectively harvest energy from manual pressing, walking, or running, which generated a current of approximately 6 μA cm –2 at an electrolyte flow rate of 40 mL min –1 over 500 cycles (Figure 14l–o). [ 333 ] The Lu group fabricated a K‐ion capacitor using commercial activated carbon, soft carbon, and potassium bis(fluoro‐sulfonyl)imide/dimethyl ether as the cathode, anode, and electrolyte, respectively, which had superior energy/power densities of 120 Wh kg –1 /599 W kg –1 and 1500 stable cycles (Figure 14p,q). [ 334 ] The Passerini group developed novel prototypes of Na/K‐ion capacitors using graphite as battery‐based anodes (reversibly intercalating solvated Na + /K + species) and activated carbons as capacitive‐based cathodes (storing/releasing anions).…”
Section: Applications Of Activated Carbonsmentioning
confidence: 99%
“…l–o) Reproduced with permission. [ 333 ] Copyright 2020, American Chemical Society. p,q) Reproduced with permission.…”
Section: Applications Of Activated Carbonsmentioning
confidence: 99%